Implementation and control of an interleaved quadratic boost DC-DC converter - Hu, Menghui (Nanyang Technological University, 2022)
Renewable energy is developing to meet the increasing energy demand. A converter is needed to step up the generated voltage to a desired value, and a controller is required to maintain the voltage level. This report presents the design, implementation and evaluation of a parallel-connected quadratic boost DC-DC converter with and without interleaved gate signals and various types of controllers. An interleaved quadratic boost DC-DC converter is formed by connecting two quadratic boost converters in parallel, and the gate signals are interleaved, i.e., the switches operate with 180° phase shift. A circuit design is implemented to generate the interleaved pulses. A non-interleaved parallel-connected quadratic boost converter shares the same gate signal for both switches. Two types of controllers, namely the sliding-mode controller and the output feedback controllers, are implemented for voltage regulation during change in desired output voltage and change in load resistance. Experimental results of the controllers are presented to show the performances of the controllers and their features.